SEEPAGE MODELING IN EMBANKMENT DAMS WITH VARIOUS SUB SOIL CHARACTERISTICS - Almaretha Mevia Azizah Putri Iswanto; Wasis Wardoyo; Trihanyndio Rendy Satrya (Institut Teknologi Sepuluh Nopember, 2022)
The embankment dam has the advantage that it can be built in all sub-base conditions although poor topography, but the weakness is seepage, so research on seepage is needed. This study uses numerical modelling with the GeoStudio program: SEEP/W and SLOPE/W. The data used is data from the Tugu Dam, Trenggalek, while the subbase data used five soil types, namely clay, silty clay, silt, silty sand, and sand. This research simulation is divided into two; the first simulation is the condition of the soil characteristics remains with the water level increasing every 5 meters from the base elevation of the dam to below the floodwater level;. In contrast, the second simulation is the condition of the water level elevation remains constant, but the soil characteristics change. Each simulation will be checked for seepage discharge and soil stability. The first simulation results show that seepage discharge and water level elevation have a logarithmic correlation with R2 > 0.75. The largest seepage discharge of 1,90 x 10-3 m3/s is sand soil, while the smallest is clay soil of 1,47 x 10-9 m3/s. The results of the second simulation show that the seepage discharge and saturated volumetric water content also have a logarithmic correlation, but some results cannot be used because they have an R2 value < 0.75. From the two simulations, the seepage discharge that occurs is said to be safe because it is below the average annual runoff which is 1% of the 10-year re-flood discharge calculated using the Nakayasu Synthetic Unit Hydrograph (HSS) which is 5.99 m3/s, and the safety factor of slope stability is > 1.2 then the dam is considered stable.